Detection of microfilariae in bactrians of Mongolia (Mongolian Journal of Agricultural Sciences, 2020)
In this study, totally 200 Bactrain camels of different ages and both sexes in Umnugobi and Dundgobi provinces of Mongolia were tested for infection with Dipetalonema evansi. Blood smears of all camels were studied for larva form of the parasite. Microfilariae were found in peripheral blood smears of 7 out of 200 (4.66%) tested camels. In contrast, out of tested camels, 1.5% were found to be infected by D. evansi. Cameline filariasis present and it might be constituted an important health problem to camels in Mongolia, resulting in impaired capacity and lowered productivity.Монгол тэмээн цусанд микрофилариа илрүүлсэн дүнгээсТэмээний филариаз нь шумуулаар дамжин халдварладаг Dipetalonema evansi (D. evansi) зүйлийн нематодоор үүсгэгддэг, эдийн засгийн хор хөнөөл ихтэй өвчин юм. Бид Өмнөговь, Дундговь аймгийн нийт 200 тэмээний цусны дээжийг түрхэцийн болон Кноттын аргаар шинжлэхэд микрофилариа (1–5.3%) илэрч байна. Тэмээнд филариазын эмнэлзүйн ил шинж тэмдэг тод ажиглагддаггүй, удаан хугацаанд өвчний үүсгэгчийг тээгч болдог нь халдвар дамжих эрсдлийг бий болгодог. Иймд эрт үед нь зөв оношилж, тохиромжтой эмчилгээг хийх шаардлагатай юм.Түлхүүр үг: Нематод, авгалдай, Dipetalonema evansi, Bactrians